2002
DOI: 10.1021/ja011931t
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxide as General Base in the Saponification of Ethyl Acetate

Abstract: The second-order rate constant for the saponification of ethyl acetate at 30.0 degrees C in H(2)O/D(2)O mixtures of deuterium atom fraction n (a proton inventory experiment) obeys the relation k(2)(n) = 0.122 s(-1) M(-1) (1 - n + 1.2n) (1 - n + 0.48n)/(1 - n + 1.4n) (1 - n + 0.68n)(3). This result is interpreted as a process where formation of the tetrahedral intermediate is the rate-determining step and the transition-state complex is formed via nucleophilic interaction of a water molecule with general-base a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 9 publications
3
40
0
Order By: Relevance
“…The conclusion that water is the actual nucleophile is also strongly supported by a proton inventory study that found that at least two hydrogen atoms are involved in the transition state. This is consistent with the general base mechanism, but not the direct attack by hydroxide [38].…”
Section: The Alkaline Hydrolysis Of Methyl Formatesupporting
confidence: 89%
“…The conclusion that water is the actual nucleophile is also strongly supported by a proton inventory study that found that at least two hydrogen atoms are involved in the transition state. This is consistent with the general base mechanism, but not the direct attack by hydroxide [38].…”
Section: The Alkaline Hydrolysis Of Methyl Formatesupporting
confidence: 89%
“…The isotope effect on the oxygen nucleophile was interpreted as a molecular event, where the attacking nucleophile in aqueous alkali is water, with general base assistance from hydroxide. The results from a proton inventory experiment for the saponification of ethyl acetate [7] agree with the mechanism proposed by Marlier. A nuclear magnetic resonance study was performed to the rates of hydroxide-promoted hydrolysis regarding formamide within an aqueous media of varying mole fraction D 2 O to shed light on whether this mechanism involves a nucleophilic attack of OH − on the C O or OH − , acting as a general base for removing protons from an attacking water.…”
Section: Introductionsupporting
confidence: 86%
“…1a). However, recent studies [7,9] found that the reactions did not occur via simple bimolecular collisions, but rather required a molecule of water to form the tetrahedral intermediate. This indicates that a water molecule stabilises the transition-state complex through hydrogen bonding (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the Arrhenius activation energies of 41.40-63.18 kJ mol À1 [3,5,6,11] for alkyl esters saponification in aqueous/protic medium were too small to account for the desolvation energy of 423.4 kJ mol À1 [9] required for the desolvation of OH À in the aqueous medium. The values of the activation energies for alky esters saponification suggest that the direct collision of desolvated OH À ions is implausible.…”
Section: Introductionmentioning
confidence: 99%